A Factorial Analysis Study on Removal of Mercury by Palm Oil Fuel Ash Adsorbent - Imla Syafiqah, Mohd Salleh; Wan Mohd Hafizuddin, Wan Yussof; Abdul Aziz, Mohd Azoddein; Shivananda, Chandraseagar; Wan Faizal, Wan Ishak (AIDIC Servizi, 2017)
Mercury is an extremely toxic pollutant that currently being emitted and distributed globally. The exposure of the mercury will mainly cause health effect and the expo sure can be in term of dose, age of person exposed and duration of exposed. One of the adsorbent can remove mercury is an activated carbon from palm oil fuel ash (POFA). POFA was used as a low cost adsorbent. An adsorbent prepared from POFA) was successfully synthesised and used to remove mercury (Hg2+) from mercury model solution in a batch process. The effects of pH [A], contact time [B], initial concentration of the Hg 2+ solution [C], adsorbent doses [D] and agitation speed [E] were screened by using response surface me thodology (RSM). A half fraction two-level factorial analysis with five factors was selected for the experimental design to determine the best adsorption conditions for mercury removal. From this study, it was found the highest mercury removal was 98.03 % at adsorbent capacity 0.10 mg of Hg 2+/g of the adsorbent with conditions of pH 2, contact time 4 h, initial Hg 2+ concentration of 5 mg/L, adsorbent doses 0.25 g and agitation speed 200 rpm. The most important factor which gives the highest percentage contribution for mercury removal efficiency is contact time [B] with 22.76 % followed by initial mercury ion concentration [C] of 5.50 %. The model obtained in this present study is significant and had a maximum point which is likely to be the optimum poin t and possible for the optimisation process later. These results suggest that POFA has a potential used as an effective, low cost, and eco-friendly green adsorbent for the removal of mercury from waste water.